Seeing Without Being Seen - Ariana Harwicz; Mikaël Gómez Guthart; Sarah Moses ([sic])
MGG: I still remember “my first time” as a translator very clearly, and fondly. In fact, it entailed two very different experiences. The first took place when I was around nine or ten years old, in the basement of a bar in the Montparnasse neighborhood in the south of Paris. It was an establishment exclusively for habitués; to get in, you had to knock on the door, and the owner would first look through the spyhole. In French, like in English, a “spyhole” is actually called a “judas” – seeing without being seen supposedly equates to betrayal. At any rate, I was there with my older brother, who didn’t speak Spanish, and a friend of my father’s from Spain, who didn’t speak French. The two were having a heated argument about the Communist Party being blind to Stalinist crimes, the lies of the Soviet regime, etc.AH: I was at the Avignon Festival once and saw a play about Stalin. During the play, Stalinist supporters outside were heard cheering for “the supreme leader.” I’d just moved to France and thought the Stalinists were part of the play, so when it was over, I congratulated them. Well, it turned out they weren’t actors. France has got to be the only country that was never communist and yet is nostalgic for communism.